Role of mifepristone in induction of labour in pregnant women with previous lower section caesarean section with IUFD in late preterm and term pregnancies - Deora, Ram Kanwar; Shetty, Nikhila G. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The objective of the study was to evaluate efficacy and safety of oral mifepristone for preinduction cervical ripening and induction of labour in late preterm and term pregnancies with previous caesarean section with intrauterine fetal demise Methods: This prospective short term study was conducted at Umaid hospital SNMC Jodhpur Rajasthan January 2016 to November 2016. 100 subjects with previous uses beyond 34 week with intrauterine fetal demise and bishop’s score<6 were included. Tablet mifepristone 200mg was given orally after taking written in informed consent. The same dose was repeated after 24 hour according to bishop’s score. Analysis was done with respect to maternal outcome of vaginal delivery, CS, duration of labour. Results: Among 100 subjects, 97 delivered vaginally (97%) delivered within 72 hour of 1% dose. Improvement of bishop’s score was observed in 1 subject (1%), which later required augmentation by oxytocin followed by vaginal delivery.1 subject (2%) failed to respond and required caesarean section, 72 hour after given of 1st dose. Conclusions: Mifepristone can be used safely and effectively for induction of labour in previous one and two LSCS near term and term pregnancies to avoid CS rates.